Method for Determining the Profile of Antibiotic Resistance Genes in the Vibrio cholera Strains by RT-PCR - A. S. Gladkikh; I. S. Fedotova; L. V. Mironova (Проблемы особо опасных инфекций, 2021)
The aim of the work was to design and carry out experimental studies of a set of reagents to identify the spectrum of genes that determine the resistance of the Vibrio cholerae strains to antibacterial drugs.Materials and methods. V. cholerae strains isolated from humans and environmental objects during epidemiological complications and the cholera-free period were included in the study. Sensitivity to antimicrobial drugs was evaluated by the disk diffusion method. Whole genome sequencing was performed on an Illumina MiSeq. The profile of resistance genes was determined based on a comparison with the ResFinder database. The temperature regime, the composition of the reaction mixtures, and the reaction parameters were optimized; the specificity, sensitivity and reproducibility of the constructed prototype test system were measured.Results and discussion. The spectrum of antibiotic resistance and the profile of resistance genes were determined for the studied strains. To develop multiplex PCR, we selected the most common in the V. cholerae populations genes, which are responsible for resistance to tetracycline (tetA), streptomycin (strA), florfenicol/ chloramphenicol (floR) and trimethoprim/sulfamethoxazole (two variants of the dihydrofolate reductase gene: dfrA1 and dhfR), as well as SXT element integrase gene (int). In the reaction, markers were specifically detected in accordance with the genomic resistance profile, which correlates with the phenotypic manifestation of resistance determined by the disco-diffusion method. The sensitivity of the developed panel of primers and probes for V. cholerae strains was 103 –104 CFU/ml. Therefore, taking into account the specificity, rapidity and simplicity of the reaction, the developed system of primers and probes can be successfully applied for a preliminary assessment of the resistance of the V. cholerae strains to antimicrobial agents.